PENGARUH KOMBINASI METODE ZILGREI DAN ENDORPHIN MASSAGE PADA IBU INPARTU PRIMIGRAVIDA TERHADAP LAMANYA KALA I FASE AKTIF DI RSUD INDRAMAYU PERIODE APRIL-MEI 2013 - Endang Nurrochmi; Nurasih Nurasih; Riqki Amaliani Romadon (Universitas Tribhuwana Tunggadewi, 2014)
The causes of high maternal mortality rate (MMR) in Indonesia are, among others, prolonged labor by 37%, excessive bleeding by 9%, fever by 7%, seizures by 2% and premature rupture of membranes (PROM) more than 6 hours by 17%. Prolonged labor can lead to infection, exhaustion, dehydration in the mother, perineal tear, asphyxia in infants, and postpartum hemorrhage. One factor causing the prolonged labor is discomfort and pain felt by women along with the progress of labor. This study aimed to determine the effect of Zilgrei methods and endorphins massage for primigravida during labor against the duration of the active phase of the first stage and to measure the labor pain intensity in the first stage of labor both during the latent phase and the active phase. This study used an analytical method with a quasi-experimental research design and nonrandomized concurrent control design. This research was conducted in Indramayu Local Hospital from 1 April to 25 May 2013. Sampling technique in this study was purposive sampling totaling 31 people. The data taken were the primary data collected directly from the study site. Analysis of the data used univariate and bivariate analysis with independent t-test for the difference between two means. Results of univariate analysis showed that the active phase of the first stage of labor in the intervention group using a combination of Zilgrei methods and endorphine massage was faster than the group given only Zilgrei method, and the pain intensity in the latent phase of the first stage and the active phase of the first stage of labor in the intervention group using a combination of Zilgrei methods and endorphine massage was lower than that in the group given only Zilgrei method. The results of the bivariate analysis showed that the variable of Zilgrei methods and endorphin massage on the duration of the active phase of the first stage obtained a P-value of 0.002 which was smaller than the value of α (0.05). Similarly, the variable of the intensity of pain in the latent phase of the first stage obtained a P-value of 0.003 which was smaller than the value of α (0.05) and the intensity of pain in the active phase of the first stage obtained a P-value of 0.001 which was smaller than the value of α (0.05). From the results of this study, it can be concluded that there was an influence of Zilgrei methods and endorphins massage for primigravida during labor on the duration of the active phase of the first stage of labor and labor pain intensity. It is recommended that health workers should be able to improve the quality of obstetric care and reduce the incidence of prolonged labor by performing the Zilgrei methods and endorphine massage.